Sabbatical leave report: academic year 2014-15 - Hochman, Will (2014)
Hochman met his goal to develop, research and write a new study on J.D. Salinger. The manuscript "Harvesting Salinger's Rye" was completed and has been submitted to various publishers. He also engaged in non-Salinger scholarship delivering conference papers on creative writing. Hochman also used the sabbatical time to make improvements in his teaching and course content and to engage in professional reading.
Keywords: dept.eng; faculty_collection; sabbatical_report

Sabbatical Leave Report - Hochman, Will (Distribution: fall-spring-15 ; English., 2015)
From the report: "My goal was to develop, reserach and write my next study on J.D. Salinger. With the aid of research and [sic] on Salinger's letters at the Morgan Library and The Firestone Library (Princeton), and several visits to his Cornish home, I was able to finish one manuscript, begin another, and start a Salinger essay designed to attract interest in my manuscript. I am happy to report that I completed my next manuscript, Harvesting Salinger's Rye, because I earned the tremendous good fortune to recieve support from SCSU."
Keywords: dept.eng; faculty_collection; sabbatical_report

Critical Companion to J.D. Salinger: A Literary Reference to His Life and Work - Mueller, Bruce F.; Hochman, Will (Facts on File library of American literature, 2011)
Keywords: Handbooks, manuals, etc; Salinger, J. D. (Jerome David), 1919-2010; dept.eng; faculty_collection